Widows and Marriage Institutions in Short Story “Perempuan Pesisir” - Ramis Rauf; Afriani Ulya; Risma Santi Rauf; Eko Harianto (AL LUGHAWIYAAT, 2020)
The main problem of this paper focused on a female major character, namely Laila who was portrayed as a weak woman that faithfully waited for her husband to return home after sailing. This paper tried to reveal how the form of misogyny towards Laila's character through a feminism perspective. The status of a widow, the husband's debt, and her baby's child were a burden of her life that must be borne by herself. The status that she carried became the trigger for the misogynistic practices. This “Perempuan Pesisir” short story explained the reality of how the domestication motives of women in Southeast Sulawesi had become global-local issues, starting from our immediate environment, the environment in the capacity of the larger community, to the wider community at the level of the state and nations. Such a topic could have just emerged in the past few decades. However, it had been tormenting women centuries ago. Thus, this short story could be a source of reference or teaching material for the initial knowledge of feminism to the people on a patriarchal basis that was deeply rooted in Southeast Sulawesi.